Pozycja starców w literaturze Ojców Syryjskich - Uciecha, Andrzej (Vox Patrum, 2011)
In this contribution author analyse certain christological and eschatological aspects of old age in writings of the Syriac Church Fathers: Testament of Adam a Christian (pseudepigraphical work from 3rd century A.D.), Acts of the Holy Apostle Thomas (the New Testament apocrypha from 3rd century A.D.), Demonstration on death and the last days of Aphrahat the Persian Sage (4th century A.D.), Hymns of Ephrem the Syrian On Paradise, On Virginity, On the Nativity, and at last one homily from Liber Graduum (a collection of 30 spiritual homelies from 5th century A.D.).